Processing of Frozen Parboiled Rice Product - Numfon Sitachitta; Kurosiyah Yamirudeng; Onanong Naivikul (Agriculture and Natural Resources, 2006)
Laboratory parboiled rice was frozen using two different freezing processes. One process was immersing the sample in liquid nitrogen (N-freezing process), then keeping it at -20°C, and the other process was direct freezing in the freezer at -20°C (F-freezing process) and keeping it there. Samples were then stored for 7 days. Comparison of various properties of cooked frozen rice samples from the two different freezing processes were done using Differential Scanning Calorimetry (DSC) to determine the thermal requirements for starch retrogradation. Hardness value of both methods increased from fresh cooked parboiled rice until day 3 after which the hardness value decreased and showed non significant difference for the freeze-thaw samples at day 7. Starch retrogradation by DSC of N-freezing process caused less enthalpy to melt the starch crystalline material than F-freezing process, especially when the time of storage and the freeze-thaw cycles of rice samples increased, but the difference was non significant for sensory evaluations. Frozen parboiled spicy rice products were processed for comparison by contact plate freezer (C-freezing process) and cryogenic freezer using liquid nitrogen as batch system (N-freezing process) before keeping in a freezer at -20°C for 5 days, and then freeze-thawed everyday. Hardness value of both frozen parboiled spicy rice processes increased from fresh cooked rice until day 3, after which the hardness values decreased and showed non significant difference for the freeze-thaw samples at day 5. There were no significant differences in sensory evaluations.